2018
DOI: 10.1075/tcb.00002.chm
|View full text |Cite
|
Sign up to set email alerts
|

Meaning and words in the conference interpreter’s mind

Abstract: The aim of the study was to examine how interpreter training and experience influence word recognition and cross-linguistic connections in the bilingual mental lexicon. Sixty-eight professional interpreters, interpreter trainees (tested at the beginning and end of their training) and bilingual controls were asked to complete a semantic priming study. Priming is a psycholinguistic research method used to examine connections between words and languages in the mind. Data analysis conducted by means of linear mixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Further evidence that translating isolated words into L2 is more demanding than translating into L1 comes from psycholinguistic reaction time studies which repeatedly reported that participants take longer to translate in the L2 direction, and the level of accuracy is much lower than in the opposite direction (Kroll & Tokowicz, 2001, p. 54). Chmiel (2018) investigated bidirectional interpreters using semantic priming in a single word recognition task and reported that despite their bilingual expertise, they showed the effect of L1 dominance. If translating single words and sentences into L2 is cognitively more demanding and error-prone than translating into L1, can this finding be extrapolated to full text translation?…”
Section: Directionality Mattersmentioning
confidence: 99%
“…Further evidence that translating isolated words into L2 is more demanding than translating into L1 comes from psycholinguistic reaction time studies which repeatedly reported that participants take longer to translate in the L2 direction, and the level of accuracy is much lower than in the opposite direction (Kroll & Tokowicz, 2001, p. 54). Chmiel (2018) investigated bidirectional interpreters using semantic priming in a single word recognition task and reported that despite their bilingual expertise, they showed the effect of L1 dominance. If translating single words and sentences into L2 is cognitively more demanding and error-prone than translating into L1, can this finding be extrapolated to full text translation?…”
Section: Directionality Mattersmentioning
confidence: 99%
“…In small translation markets where the home language has a low diffusion translators need to be versatile and translate into their L1 and L2, that is they provide services in bidirectional translation (Pavlović 2007b;Whyatt and Kościuczuk 2013;Ferreira and Schwieter 2017;Chmiel 2018). It seems intuitive that when translating into L2, translators will rely more on external support -now this support usually comes from online resources (henceforth OR).…”
Section: Introductionmentioning
confidence: 99%